Prognostic factors and the impact of adjuvant chemotherapy on recurrence and survival in stage I non-small cell lung cancer: A real-world study - Doğan, Akif; Yıldırım, Sedat; Erölmez, Hande Nur; Akdağ, Goncagül; Yüksel Yaşar, Zeynep; Türkoğlu, Ezgi; İlhan, Nurullah; Ay Ersoy, Seval (The European Research Journal, 2025)
Objectives: Non-small cell lung cancer (NSCLC) is a leading cause of cancer-related mortality. Despite curative surgery, recurrence is common in Stage I NSCLC, highlighting the need for improved prognostic classification. This study aims to evaluate the key pathological factors affecting recurrence and survival and to investigate the potential benefit of adjuvant chemotherapy (ACT) in patients with Stage I NSCLC. Methods: A retrospective analysis was conducted on patients with Stage I NSCLC who underwent curative surgery between 2010 and 2024. Demographic and disease-related prognostic factors were assessed. The impact of these factors, along with adjuvant chemotherapy (ACT), on overall survival (OS) and disease-free survival (DFS) was analyzed. Results: A total of 95 patients were included in the study, with a median follow-up period of 47 months. Recurrence occurred in 35.8% of patients, and 16.8% died. The five-year OS and DFS rates were calculated as 76.4% and 67.9%, respectively. Spread through air spaces (STAS) was identified as an independent prognostic factor associated with an increased risk of recurrence. While OS was shorter in patients with LVI positivity, it was not determined to be an independent prognostic factor. Visceral pleural invasion (VPI) did not demonstrate a significant prognostic impact on survival or recurrence. The effect of ACT on OS and DFS was evaluated, but no survival advantage was observed. Conclusions: Certain pathological factors influence survival and recurrence in Stage I NSCLC. While STAS was identified as an independent prognostic factor, ACT did not provide a significant benefit for OS or DFS. These findings emphasize the importance of individualized treatment approaches and close oncological follow-up after surgery. Future studies should incorporate novel and effective biomarkers, such as circulating tumor DNA, to optimize adjuvant therapy decisions.